Economic Valuation of Household Waste Transportation in Yogyakarta City, Indonesia: A Contingent Valuation Approach - Anggi Rahajeng; Yudistira Hendra Permana; Naufal Mohamad Firdausyan; Sulistyo Handoko (School of Postgraduate Studies, Diponegoro Univer, 2026)
This study examines the economic aspects of solid waste management in Yogyakarta City by comparing households' Ability to Pay (ATP) and Willingness to Pay (WTP). Using survey data and Tobit regression analysis, this research estimates ATP and WTP values and identifies their underlying determinants. The findings reveal a crucial phenomenon: WTP consistently exceeds ATP. This indicates that while citizens highly value waste services and are willing to pay more, they are restricted by their actual financial capacity. Furthermore, demanding physical obligations, such as mandatory sorting for waste banks, significantly reduce WTP because households perceive this manual effort as an added burden. Given that Yogyakarta City currently lacks a standardized tariff system, this study warns that implementing a uniform flat-rate tariff in the future would be highly inequitable. A flat-rate system would severely burden vulnerable groups while disproportionately benefiting wealthy households. Therefore, the government is advised to implement a progressive, tiered tariff system. Through cross-subsidization, wealthier households would pay a premium to subsidize low-income populations. This equitable financing scheme is absolutely necessary to ensure the commercial viability and sustainability of Public-Private Partnership (PPP) projects under the 2022–2031 waste management masterplan.